Different structure transitions and tensile property of LLDPE film deformed at slow and very fast speeds. (June 2018) - Du, Wenjie; Ren, Yi; Tang, Yujing; Shi, Ying; Yao, Xuerong; Zheng, Cui; Zhang, Xiaohong; Guo, Meifang; Zhang, Shijun; Liu, Li-Zhi
Graphical abstract: Highlights: Visible crazes observed for fast stretching but not for slow stretching. Crazes initiated uniformly for fast MD tensile, but not for fast TD tensile. A much faster structure change is observed during the fast stretching process. The leaning is helpful to better understand the puncture, dart and tear of PE films. Abstract: In the present work, the uniaxial deformation of 1-hexene based Linear Low Density Polyethylene (LLDPE) cast film at slow to very fast stretching speed (initial strain rate 10 −3 to 8.3 s −1 ) was investigated, together with a high speed video camera for capturing craze morphologies. The structural evolution of the deformed film at different speeds was also studied with Small Angle X-ray Scattering. Very different tensile behavior is observed when the film is stretched at very fast speed. Voids are detected by SAXS for slow MD and TD stretching processes; but no visible crazes are observed. However, visible crazes appear starting at a small satrain of 0.3 during fast MD stretching, due to the film being more rigid when stretched at the fast speed. The crazes appear with the length direction being perpendicular to the stretching direction and propagate quickly in the length direction. The crazes appear almost everywhere in the film during the fast MD stretching, while only occur in the central region during the fast TD stretching due to the preferred crystal orientation in MD direction where crazes can propagate more easily and faster. The structure transition at lamellar level is much faster during the fast stretching process, due to the formation of the visible crazes. The leaning is helpful for better understanding puncture, dart and tear tests of PE films, where the films undergo the fast deformation.